Neutropenic acute acalculous cholecystitis (AAC) in a 12-year-old boy with T-acute lymphoblastic leukemia successfully managed with conservative treatment. (2nd January 2017) - Naselli, Aldo; Bishop, Hugh; Walker, Shonagh; Warris, Adilia
ABSTRACT: Acute acalculous cholecystitis (AAC) is an inflammation of the gallbladder without the presence of gallstones. In children with malignancies or chemotherapy-induced neutropenia, AAC is very rare. Clinical diagnosis of AAC remains difficult in this patient population but an early recognition followed by an appropriate intervention may confer a benefit. Only three pediatric patients with underlying hematological malignancies whose clinical treatment course was complicated by the development of AAC have been described. We describe a neutropenic pediatric patient who developed AAC following chemotherapy for acute T-cell acute lymphoblastic leukemia (T-ALL), which was successfully managed with conservative treatment. Abbreviations: AAC: Acute acalculous cholecystitis; T-ALL: T-cell acute lymphoblastic leukemia; TPN: Total parenteral nutrition